The enduring importance of family wealth: Evidence from the Forbes 400, 1982 to 2013 - Philipp Korom; Mark Lutter; Jens Beckert (Max Planck Institute for the Study of Societies, 2015)
The social science literature proposes two competing explanatory frameworks for the existence and longevity of super-fortunes: superstar or winner-take-all mechanisms, suggesting an increased dominance of new self-made billionaires; and mechanisms focusing on inherited advantages, suggesting an enduring importance of old family fortunes. Using panel data from the USA's annual Forbes 400 ranking (1982-2013), this study analyzes factors that increase or decrease the likelihood of remaining listed among the American super-rich. We find initially that the percentages of self-made entrepreneurs among the highest wealth echelons of US society have increased significantly since 1982. Sectors that improved the most are finance (including hedge funds and private equity), new technology and mass retail. The decline of inheritance as a source of wealth and the rise of new tech and finance fortunes suggest low reproduction rates among super-rich property owners. Family wealth, however, plays an important role if the longevity of fortunes is considered. While the literature predicts family fortunes to be taxed away, divided among a large number of heirs, or lost through incompetence, we find that scions of inherited great wealth (mostly up to the third generation) are more likely to remain listed in the Forbes 400 roster than self-made entrepreneurs. We conclude that even though entrepreneurship increasingly matters for becoming super-rich, it is first and foremost the ability of rich family dynasties to retain control over corporations and to access sophisticated financial advice that makes fortunes last. – – Die sozialwissenschaftliche Literatur zur Existenz und Langlebigkeit von Superreichtum bietet zwei konkurrierende Erklärungsansätze: zum einen Superstar- oder Winner-take-all-Mechanismen, die zu einer Zunahme von Selfmade-Milliardären führen; zum anderen aus ererbten Vorteilen entstehende Mechanismen, aus denen sich eine fortlaufende Konzentration alter Familienvermögen ergibt. Mithilfe eines Längsschnittdatensatzes aus den Forbes-400-Listen von 1982 bis 2013 untersucht das Papier, von welchen dieser Faktoren die Verweildauer im Forbes-Ranking abhängig ist. Dabei zeigt sich zunächst, dass der Anteil des Selfmade-Unternehmertums in den Rankings seit 1982 deutlich ansteigt. Die Branchen mit dem höchsten Wachstum sind die Finanzwirtschaft, insbesondere Hedge-Fonds und Private-Equity-Firmen, sowie neue Technologien und Handel. Auch wenn dies auf eine abnehmende Bedeutung ererbten Familienvermögens hinweist, zeigt sich bei der Analyse der Verweildauer, dass Erben großer Vermögen (meist in dritter Generation) deutlich länger in den Rankings verbleiben als Selfmade-Unternehmer. Wir schließen daraus, dass es trotz der Zunahme von Selfmade-Superstars in erster Linie Familiendynastien sind, denen es gelingt, durch Firmenbesitz und professionelle Vermögensberatung die Kontrolle über ihren Reichtum aufrechtzuerhalten.
Keywords: 300